Effects of Medial-Lateral Glide Versus Radius Anterior Glide in patients with Lateral Epicondylistis - Shazia Bashir, Bilal Umer, Hafiz Muhammad Asim, Wajeeha Zia, Muhammad Umer Arshad, Sarfraz Ahmad (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To Compare Ulnar Medial Lateral Glide and Radius Anterior Glide for Improving Lateral epicondyle tendinopathy. Study design: Randomized Clinical Trial Methods: Data was taken through Non-Probability Convenience Sampling Technique. Subjects with nonspecific lateral epicondyle tendinopathy were randomly allocated to 2 groups; one taking medial lateral glide, other anterior radial glide. Baseline, after-treatment two readings were taken through Numeric Rating Pain Scale and lateral epicondyle tendinopathy symptoms. Data was analyzed through Statistical Package for Social Sciences 25.00. Results: The findings showed between group comparisons at 1streading for lateral epicondylitis. The p value was 0.896 showing no statistically significant difference in effects of both treatments. P value 0.929 verifies this fact. The average difference that found was 0.0757. The p value was 0.907 showing statistically significant difference in effects of both treatments.P value 0.819 verifies the fact too. The average difference found to be 0.7926. Furthermore, the findings showed between group comparisons of. Average difference at pre-treatment and 1stafter treatment reading, pre-treatment and second after treatment reading, pre-treatment and third after treatment reading were 0.831, 0.02 and 0.00 respectively. Conclusion: The study concluded that there was no significant different in outcomes of medial lateral glide and anterior radial glide in improving tendinopathy in lateral epicondylitis Keywords: Anterior Radial Glide, Medial Lateral Glide, Lateral Epicondylitis, Tendinopathy, Tennis Elbow